Tinjauan Kebijakan: Evaluasi Efektivitas Upaya Penanggulangan Bencana di Desa Ciwangi - Abraham Ritonga (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
Ciwangi Village in Garut Regency, has the potential for disasters such as earthquakes, floods, and landslides. Therefore, evaluating the effectiveness of disaster management efforts in Ciwangi Village is crucial for mitigating risks and protecting local communities. This research aims to explore the dynamics of disasters that occurred in Ciwangi Village and evaluate the level of effectiveness of mitigation policies, starting from the structural level to the village. This research uses qualitative methods by reviewing Regional Regulations (Perda) related to disaster management in Ciwangi Village, Garut Regency. The review was carried out using in-depth interviews, observations, and document analysis. The analysis was carried out by detailing the implementation of the Sendai Framework for Disaster Risk Reduction (SFDRR) principles at the local level. The results of the analysis are then linked to Chamber Theory to evaluate the effectiveness of policy coordination and implementation at the village level. The research results show that disaster mitigation efforts in Ciwangi Village are still weak in terms of understanding disaster risk, disaster risk management, investment in disaster risk reduction, and disaster preparedness.